Elaboración de bloquetas ecológicas para muros no portantes a partir de residuos plásticos como alternativa sostenible en la construcción - Sanchez Contreras, Gustavo Adolfo; García Bandach, Daphnne Isbell Magdriel; Mejía Marquina, Gianella Sofia; Cuya Rodríguez, Daniela Nicole (LACCEI, 2025)
This article presents an experimental proposal for the production of eco-friendly bricks made from plastic waste, specifically polyethylene terephthalate (PET) and polypropylene (PP), as a sustainable alternative to conventional construction materials. The main objective was to evaluate the technical and environmental feasibility of a small-scale prototype suitable for non-load-bearing enclosures and interior applications. Several tests were carried out using mixtures of PET, PP, sawdust, and synthetic glue, revealing limitations in cohesion and durability in the initial formulations. The optimal combination was achieved using only recycled plastics. The study demonstrates the potential for plastic waste valorization through simple processes, promoting circular economy principles and generating environmental, social, and economic benefits. This approach is replicable in urban contexts with high volumes of plastic waste and can be integrated into community initiatives or sustainable construction projects.